Risk Management in Micro, Small, and Medium Enterprises: An Empirical Analysis of SMEs Dried Fish in Bengkulu Province - Ketut Sukiyono; Muhamad Mustopa Rhomdon; Musriyadi Nabiu; Nola Windirah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research